2018
DOI: 10.2340/00015555-2833
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Dermatology Life Quality Index and Psoriasis Area and Severity Index in Patients with Psoriasis Treated with Ustekinumab

Abstract: Monitoring of biological treatment efficacy for psoriasis is based on clinical evaluation and patient's quality of life. However, long-term correlation between Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI) in real life has not been studied in patients treated with ustekinumab. All patients with psoriasis treated with ustekinumab at our department were included (n = 120) in this study. Correlation analyses between the change in PASI and DLQI and the individual subquestions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 12 publications
(15 reference statements)
4
20
0
Order By: Relevance
“…In the current study, correlations between changes in PASI and DLQI were highly dependent on how these changes were assessed; relative changes in both PASI and DLQI yielded the highest correlation coefficient, and relative changes in PASI and absolute changes in DLQI the lowest. The correlations were similar to those reported in previous studies (13,14,29). Patients achieving higher PASI response had lower mean DLQI and higher reductions in absolute DLQI.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the current study, correlations between changes in PASI and DLQI were highly dependent on how these changes were assessed; relative changes in both PASI and DLQI yielded the highest correlation coefficient, and relative changes in PASI and absolute changes in DLQI the lowest. The correlations were similar to those reported in previous studies (13,14,29). Patients achieving higher PASI response had lower mean DLQI and higher reductions in absolute DLQI.…”
Section: Discussionsupporting
confidence: 88%
“…The first question on "Symptoms and feelings" demonstrated the strongest correlation with PASI, and changes in PASI for the individual questions of DLQI, and contributed most to the overall DLQI. Previous studies have demonstrated weak correlations between relative changes in PASI and DLQI from baseline to weeks 10-16 (13,14), moderate correlation for percentage changes in both PASI and DLQI (29) and in a systematic review of randomized clinical trials (RCT) a strong correlation was demonstrated between mean percentage reduction in PASI and mean reduction in DLQI (34). In the same review patients achieving PASI75 showed clinically meaningful higher reductions in mean DLQI compared with those achieving PASI50-75 and PASI < 50 (34) and in RCTs, patients achieving PASI90 reported lower DLQI than those achieving PASI75-89 (11), and a higher proportion of patients achieving PASI100 report a DLQI of 0 or 1 compared with patients achieving PASI75-< 100 (35).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…4 Several studies have demonstrated various degrees of correlation between PASI response and DLQI improvement; however, the DLQI is not specific for psoriasis. [5][6][7][8][9] In the pivotal VOYAGE 1 and 2 clinical trials of guselkumab in psoriasis, clinician-determined PASI and IGA outcomes were highly correlated with DLQI; 10,11 however, about 20% to 30% of patients achieving clear skin (ie, 100% improvement in PASI score [PASI 100]) still reported a DLQI score >1 in VOYAGE 1, indicating psoriasis still had an impact on daily life. 12 Recently, greater emphasis has been placed on patientreported assessments of the severity of psoriasis and improvement after treatment.…”
Section: Introductionmentioning
confidence: 99%